Investigating English Teachers Perceptions and Practices of TBLT in Three Secondary Schools in Awi Zone - Addis, Ketema; Yigzaw, Abiy (Asian Journal of Contemporary Education, 2018)
The purpose of this study was to investigate teachers’ perceptions and practices of Task-Based Language Teaching (TBLT) in Awi zone three secondary schools. The data for this study were collected through questionnaires from a total of 32 teachers at three secondary schools in Awi zone. The sample of the study was taken by using convenience sampling method. In order to gather data from the subjects of the study; questionnaire, interview and class room observation were used. The internal consistency of the questionnaire proved by Cronbach’s alpha. Both qualitative and quantitative methods of data analysis were employed. SPSS version 17.0 Windows was used to analyze the results of the questionnaire. One sample t-test was used to assure whether the observed and the expected mean score differences were significant. The statistical data analysis was descriptive and inferential. Frequency, a percentage analysis and mean scores were used. The data that was gathered from the class room observation and interview were qualitatively analyzed. The analysis provided qualitative data which is exploratory, explanatory and interpretive in nature. Findings of the study revealed that the study of perceptions and their practices demonstrated that TBLT has not been implemented successfully within three secondary schools in Awi zone as teachers have only limited perception and incomplete practice of its theories and methodologies. The challenges and possibilities towards the implementation of TBLT in the class room are identified. Finally, some recommendations were forwarded based on the main findings of the study.